Different cooling strategies between sets for 30 seconds does not have beneficial effect on resistance exercise with blood flow restriction - Rodrigo Luiz da Silva Gianoni; Paulo Eduardo Pereira; Paulo Henrique Azevedo (Revista da Educação Física)
The ice application (cooling) has become popular during physical activities to improve performance. This study aimed to test whether different cooling places could increase the number of repetitions (volume) during resistance training with blood flow restriction (BFR). Ten women volunteered for this study. The sample characterization is presented in mean and standard deviation: age: 28.5 ± 8.6 years; height: 164.6 ± 8.3 cm; total body mass: 61.5 ± 7.1 maximal dynamic strength test (1RM): 236.5 ± 54.8 kg; 30% 1RM: 71.6 ± 16.5; SBP: 124.7 ± 7.7 mm Hg; 1.3 x SBP: 161.8 ± 10.4 mm Hg. The subjects performed five sessions of resistance exercise with BFR. Three sets were held in each session, with the intensity of 30% of 1RM until muscle failure; and 30-second rest period between sets. The cooling sites were: hands, neck, and tunnel temperature. One session without cooling was done and considered as a control group. There was neither difference in the total number of repetitions of repetitions among interventions, nor a significant difference among interventions for RPE (P = 0.49). Therefore, we do not recommend cooling to maintain a high number of repetitions during strength training with BFR.